Comunicação organizacional inclusiva: o pertencimento dos surdos às organizações - Veronezi, Daniela Priscila de Oliveira (2022)
This investigation has as its object organizational communication, focusing on the inclusion of Deaf employees in the corporate environment. According to some scholars, based on the understanding of the Deaf community itself, the use of the Brazilian Sign Language (Libras) is the differentiating element between people with hearing impairment (who do not use it) and the Deaf, who communicate through it. However, this distinction often does not reach the legislative scope, which generally uses the expression “person with disabilities” and includes the Deaf among these subjects. It starts from the idea that inclusion, as a social practice, has as a prerequisite the transposition of communication barriers and the feasibility of interactions between subjects in their diversity. In Brazil, the great milestone in the achievement of Deaf rights is Law nº 10.436/2002, regulated by Decree nº 5.626/2005, which recognizes Libras as a legal means of communication and expression. Law nº 8.213/1991 is also worth mentioning, which establishes quotas for people with disabilities in organizations and contributes to a continuous, albeit incipient, movement of the Deaf towards these spaces of sociability. However, being in organizations, by legal obligation, does not automatically mean feeling belonging and included in them. In this sense, this investigation proposes the constitution of an inclusive organizational communication, which presupposes the recognition of the Deaf as subjects that must be known in their specificities and for which communication professionals need to devise strategies capable of reaching them, awakening in the Deaf the feeling of belonging to the corporate environment. Bearing in mind the importance of communication for social inclusion to become a reality, the Brazilian Law for the Inclusion of Persons with Disabilities brings with it barriers in communication and information that make the implementation of this process difficult. Furthermore, these mishaps related to communication are addressed by renowned researchers who are dedicated to the studies of inclusion, even in other areas of knowledge. With this, this research presents the following problem question: How can the communication professional contribute to the Deaf to feel part of organizations? This question, in turn, unfolds into: What procedures should be adopted to implement inclusive organizational communication? What difficulties do Deaf people face daily to develop their work? What measures have been effectively taken by organizations towards inclusive communication? Regarding the methodological aspects, it is an exploratory study, with the aim of deepening knowledge or making new discoveries. In order for the desired results to be, in fact, achieved, this investigation uses bibliographic and documentary research, as well as interviews, through semi-structured scripts, and the application of questionnaires, which are scrutinized based on the method of analysis of content. As a result, the study demonstrates that the inclusion of the Deaf, as a social practice, is permeated in its essence by communication and, in this context, it emerges as a promising field of research for studies developed in the context of organizational communication.